ANALISIS TREN HARGA SAHAM PT UNILEVER INDONESIA PERSPEKTIF NET PROFIT MARGIN, EARNING PER SHARE DAN CURRENT RATIO - Rita Satria; Nina Shabrina (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This research aims to determine the effect of Net Profit Margin (NPM), Earning Per Share (EPS) and Current Ratio (CR) on Stock Prices at PT Unilever Indonesia Tbk for the 2010-2020 period. This research method is a quantitative research method, the population of this study is the financial statements of PT Unilever Indonesia Tbk for the period 2010-2020 and the sample data comes from the balance sheet, income statement and stock price report at PT Unilever Indonesia Tbk for the 2010-2020 period. The results of the t-test in this study showed that the Net Profit Margin (NPM) had a tcount value of -1.468 < from the ttable value of 2.36462 with a significant value of 0.186 > 0.05, meaning that Net Profit Margin (NPM) had no significant effect on prices. shares, while the results of Earning Per Share (EPS) have a tcount of 4.229 > from a ttable value of 2.36462 with a significant value of 0.004 <0.05, meaning that Earning Per Share (EPS) has a significant effect on stock prices. Then the Current Ratio (CR) obtained a tcount value of 0.055 < from a ttable value of 2.36462 with a significant value of 0.958> 0.05 meaning that the Current Ratio (CR) had no significant effect on stock prices. While the results of the F test obtained the Fcount of 10.233 > Ftable 4.35 with a significant value of 0.006 <0.05, meaning that Net Profit Margin (NPM), Earning Per Share (EPS) and Current Ratio (CR) simultaneously have a positive and positive effect. significant to stock prices and the coefficient of determination is 73.5%, meaning that there is a strong level of relationship.